The Arab Nahdah : the making of the intellectual and humanist movement - Patel, Abdulrazzak (Edinburgh studies in modern Arabic literature., 2013)
To understand today's Arab thinking, you need to go back to the beginnings of modernity: the nahdah or Arab renaissance of the 19th and early 20th centuries. Abdulrazzak Patel enhances our understanding of the nahdah and its intellectuals, taking into account important internal factors alongside external forces. Patel explores the key factors that contributed to the rise and development of the nahdah. He introduces the humanist movement of the period that was the driving force behind much of the linguistic, literary and educational activity. Drawing on intellectual history, literary history and postcolonial studies, he argues that the nahdah was the product of native development and foreign assistance and that nahdah reformist thought was hybrid in nature. Overall, this study highlights the complexity of the movement and offers a more pluralist history of the period.